FACTORS AFFECTING EMPLOYEE RETENTION: A CASE STUDY OF TAN PHU LOGISTICS COMPANY IN HO CHI MINH CITY, VIETNAM - Pham , Van Tai; Le , Thi Van (International Journal of Psychosocial Rehabilitation, 2020)
This research was conducted at a Vietnamese logistics company which has experienced low employee retention in the past five- year 2015 – 2019. The purpose of the study is to examine major factors influencing the employee retention at the company as well as give some recommendations for improving employee retention issue. In order to write the article, consulting several sources such as books, newspapers, magazines, reports as well as other articles was necessary. Both qualitative and quantitative research are applied in the study.